The effect of emotional intelligence on burnout and the impact on the nurses service quality - Agustina Hanafi (Journal of Economics, Business, and Accountancy Ventura, 2016)
This study attempts to analyze the effect of emotional intelligence on emotional exhaustion and this, in turn, on the quality of hospital care nurse. The subjects were nurses and patients RS RK.Charitas Palembang. This sample was taken using Non-Probability Sampling towards the nurses and patients in the patient units of the hospital Joseph 1 & 2, with the total respondents of 200 people. These were selected as sample and the data analyzed through the process using Structural Equation Model (SEM). It shows that emotional intelligence negatively affects the emotional exhaustion. Furthermore, the emotional intelligence has positive effect on the quality of nursing care. Most importantly, there is a greater direct effect of emotional intel-ligence towards service quality than the indirect effect through the emotional ex-haustion. Emotional exhaustion negatively affects the quality of nursing services.